2012
DOI: 10.1021/ef300405g
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Methane Sorption Isotherms of Black Shales from The Netherlands

Abstract: High-pressure methane sorption isotherms were measured on one Paleozoic and five Mesozoic shales, considered as targets for shale gas exploration in The Netherlands. The samples varied in mineralogy, organic richness, and thermal maturity. Four of the samples were clay-rich (total clay content 60−71 wt %), one contained equal amounts of clays and quartz (36 wt % and 33 wt %, respectively) and one was a marl sample (clays 34 wt %, carbonates 49 wt %). The total organic carbon contents (TOC) ranged from <1 wt % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
355
2
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 488 publications
(399 citation statements)
references
References 30 publications
32
355
2
10
Order By: Relevance
“…This is consistent with experimental measurements [70]. Qualitatively, the maximum excess sorption of methane has been observed in studies on dried gas shales by Gasparik et al [71], as is shown in the right hand side of Figure 16; in their work, maxima in the excess isotherms were observed for all but the leastmature sample. However, it is possible that the adsorption on gas shales is more complex than adsorption on kerogen, as the clay minerals present a significant surface area in these samples.…”
Section: A) B)supporting
confidence: 91%
“…This is consistent with experimental measurements [70]. Qualitatively, the maximum excess sorption of methane has been observed in studies on dried gas shales by Gasparik et al [71], as is shown in the right hand side of Figure 16; in their work, maxima in the excess isotherms were observed for all but the leastmature sample. However, it is possible that the adsorption on gas shales is more complex than adsorption on kerogen, as the clay minerals present a significant surface area in these samples.…”
Section: A) B)supporting
confidence: 91%
“…Within the phyllosilicates group, illiterich mixed layer illite-smectite is the most prominent component, followed by kaolinite, illite, muscovite and chlorite. In addition, there is a moderate content of quartz (8)(9)(10)(11)(12)(13)(14)(15)(16) wt.%) and minor contents of pyrite (4-9 wt.%), feldspars (1-5 wt.%) and dolomite (0.3-6.4 wt.%).…”
Section: Mineralogymentioning
confidence: 99%
“…11 Although sorption data on shales are available, the absolute sorption capacity in shale remains poorly constrained. [11][12][13][14][15][16][18][19][20] Shales are complex heterogeneous materials with amorphous kerogen and inorganic phases. The amounts of methane adsorbed on shales are also very low and this is complicated by the fact that the minor kerogen component has a much larger adsorption capacity than the inorganic phase in the shale.…”
Section: Introductionmentioning
confidence: 99%
“…Montgomery et al, 2005;Gasparik et al, 2012;Rexer et al, 2013). Organic matter contents in the Holywell Shale only average 1.9 wt % and only a small portion of the Formation has TOC contents above 3 wt %.…”
Section: Reservoir Qualitymentioning
confidence: 99%